BZT305- Vertebrate Zoology (Zoologi Vertebrata) - PPSKJ, Pusat Pengajian Sains Kajihayat (Universiti Sains Malaysia, 2023)
First Semester Examination 2022/2023 Academic Session February 2023 BZT305- Vertebrate Zoology (Zoologi Vertebrata) Duration : 2 hours (Masa : 2 jam)